RANCANG BANGUN SISTEM INFORMASI ADMINISTRASI PKM UNIVERSITAS LAMPUNG BERBASIS WEB MENGGUNAKAN METODE RATIONAL UNIFIED PROCESS (RUP) - Ayu Taqiya Ulfa; Astria Hijriani; Rico Andrian (Universitas Lampung, 2018)
Administrative information system of the Program Kreativitas Mahasiswa (PKM) of Lampung University is a web-based information system developed to assist administrative process in the implementation of PKM at university level, to record participants of PKM University of Lampung, to disseminate information about PKM, and to provide reference of PKM document of University of Lampung students. Information system administration PKM University of Lampung was developed using the programming language PHP and MySQL. The system development method used is the Rational Unified Process (RUP) method. The RUP divides one development cycle into four phases. The phases of the RUP are inception, construction, elaboration, and transition. Each phasein the workflow process that starts from business modeling,requirement,analysis and design, implementation,testing, and finally deployment. The process in the inception phase is business modeling and requirement, then at elaboration stage is analysis and design and implementation. The process at the construction phase is testing, then process at thetransition phase is deployment. Software product testing is done by equivalence partitioning testing and alpha test version. Test results reached success rate 91.41%, so it can be concluded that the functions on the system running well and the system can already to use.